Integrating Pancasila philosophy into arts education curriculum design - Hadi, Sumasno; Rachmat , Rachmat; Sulisno, Sulisno (Pascasarjana Institut Seni Indonesia Surakarta, 2024)
When national education policy in Indonesia first included art as a content of the formal learning curriculum, art learning in schools has generally underwent many developments. The dynamics of its development also raise conceptual and practical issues, one of which is about the basic paradigm of art education in higher education (universities) that prepare art teachers in public schools. This research aims to find the educational philosophy that underlies and emphasizes the concept of art education in Indonesia so that it can guide the formulation of the curriculum content of art lessons in schools. This research uses the hermeneutic-philosophical method through three steps: finding and describing concepts, systematizing concepts, and then testing the level of explanation of the resulting concept system. Based on the results of the research, it is known that the philosophy of art education in Indonesia refers to the cultural values of the Indonesian nation formulated in the philosophy of Pancasila and the opening of the 1945 Constitution. The paradigm of art education in Indonesia must also be based on the philosophical concepts of Pancasila. The implication is that the concepts of formal art education in Indonesia, which include goals, curriculum content, students and educators, as well as the socio-cultural environment, must integrate the values of Pancasila.